Responses of the submerged macrophyte Vallisneria natans to elevated CO2 and temperature - J Cao (Inter-Research, 2015)
Inorganic carbon and temperature are 2 important factors that regulate the growth of submerged macrophytes. However, experimental evidence regarding the eco-physiological changes that occur in submerged macrophytes in response to elevated CO2 and temperature is still limited. To investigate how the submerged macrophyte Vallisneria natans (Hydrocharitaceae), a common species in the waters of the middle and lower reaches of the Yangtze River, responds to these factors, we conducted a mesocosm experiment using simulated CO2 elevation (by bubbling CO2 into experimental water) and ambient temperature warming systems. During the 60 d experiment, CO2 elevation significantly increased the inorganic carbon concentration in the water column. The warming systems elevated average water temperature by approximately 3°C. The elevation of CO2 levels significantly enhanced the photosynthetic performance, growth and clonal propagation of V. natans. When combined with an increase in CO2, elevated temperatures also promoted photosynthesis and growth. The individual ramet biomass of V. natans decreased with increasing temperature, but only significantly under ambient CO2 levels. CO2 elevation increased both stolon elongation and bud number. At elevated CO2 concentration, more biomass was allocated to the stolons, roots and buds, while less biomass was allocated to the leaves. These results indicate that the eco-physiological responses of V. natans should increase its stress tolerance in aquatic plant communities under future spatial and temporal variation in CO2 levels, however, further research is required.